(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic caused alterations within all aspects of human life, which enabled students to uncover fears. These negative emotions, even for training nursing students, can become contagious within and between families, family members and friends, dominating and clouding their judgment. So, how do you manage fear? This study aims to describe the experience of five graduating nursing students and their respective teacher in rebuilding and promoting positive emotions (e.g. optimism, hope, courage) through a digital tool (a Blog) throughout the imposed quarantine time. A descriptive study, experience report type, analyse the authors lived experiences during the mandatory quarantine period that emerged due to COVID-19 virus, between March and May of 2020. Symbolic interactionism is used as a philosophical base that guided data collection and analysis. Through the report of their lived experiences, we encountered that the Blog empowered teacher and students to achieve their goals and find new meanings in their lives through three spiritual paths: compassion and kindness; self-awareness and courage. All participants agreed that this kind of digital tool should be used throughout the bachelor´s in nursing, which generates a more humanized way of teaching, allowing students to see beyond University walls.